The Effect of Debt-Based Financing and Equity-Based Financing on Profitability of Islamic Banks in Indonesia - Wahyudi, Rofiul; Aulia Arifatu Diniyya; Julia Noermawati Eka Satyarini; Lu’liyatul Mutmainah; Sri Maulida (International Journal of Islamic Business and Economics (IJIBEC), 2020)
This study's main objective was to investigate the equity-based financing and debt-based financing on the profitability of Islamic banking in Indonesia. This research was expected to provide contribution to both theoretical and practical dimensions. Based on the theoretical dimension, this study can provide evidence whether equity-based financing and debt-based financing affect profitability of Islamic banking. Meanwhile, based on practical dimension, Islamic banks in Indonesia can determine their extensive profitability and, in turn, the competitiveness of Islamic banks is able to be developed in line or even better than that of conventional banks. The data were analyzed using a panel regression technique with data time series and cross-section. Furthermore, the panel data model was estimated by common effect, fixed effect, and random effect. The result of this study showed that equity-based financing partially did not affect ROE. At the same time, debt-based financing affected ROE of Islamicbanks. Equity-based financing and debt-based financing partially did not affect ROA of Islamic banks. However, The test results of both independent variables, consisting of equity-based financing and debt-based financing, simultaneously had a strong influence on the dependent variable, that is, profitability, as measured by ROA and ROE.